2016
DOI: 10.1007/s12041-016-0642-1
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian logistic regression in detection of gene–steroid interaction for cancer at PDLIM5 locus

Abstract: The PDZ and LIM domain 5 (PDLIM5) gene may play a role in cancer, bipolar disorder, major depression, alcohol dependence and schizophrenia; however, little is known about the interaction effect of steroid and PDLIM5 gene on cancer. This study examined 47 single-nucleotide polymorphisms (SNPs) within the PDLIM5 gene in the Marshfield sample with 716 cancer patients (any diagnosed cancer, excluding minor skin cancer) and 2848 noncancer controls. Multiple logistic regression model in PLINK software was used to ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…29 Wang et al further revealed that the SNP rs6532496 of the PDZ and LIM domain 5 gene, which may play an important role in the pathomechanisms of bipolar disorder and major depressive disorder, was strongly related to the overall cancer risk. 30 Second, both patients with bipolar disorder and their unaffected siblings are more prone to certain carcinogenic factors, including smoking, obesity and diabetes mellitus, than in the general population. [31][32][33] In our previous study, the unaffected siblings of bipolar probands were younger age at the time of diagnosis of type 2 diabetes mellitus than were the controls.…”
Section: Discussionmentioning
confidence: 99%
“…29 Wang et al further revealed that the SNP rs6532496 of the PDZ and LIM domain 5 gene, which may play an important role in the pathomechanisms of bipolar disorder and major depressive disorder, was strongly related to the overall cancer risk. 30 Second, both patients with bipolar disorder and their unaffected siblings are more prone to certain carcinogenic factors, including smoking, obesity and diabetes mellitus, than in the general population. [31][32][33] In our previous study, the unaffected siblings of bipolar probands were younger age at the time of diagnosis of type 2 diabetes mellitus than were the controls.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a point mutation on Cypher 's LIM domains increases the binding affinity for PKC and is associated with DCM of patients carrying this mutation . Although no studies have yet reported the association between PDLIM5 mutations and cardiomyopathy, PDLIM5 gene mutations may actually lead to an increased susceptibility to diseases such as cancer, bipolar disorder, hypertension, alcohol dependence and schizophrenia …”
Section: Discussionmentioning
confidence: 99%
“…In central neurons, PDLIM5 is mainly localized in the membrane and cytoplasm, where it regulates neuronal calcium signaling and co-localizes with neurotransmitter-protruding vesicles (Numata et al, 2007); these observations indicate that PDLIM5 plays a role in brain development. Some studies have shown that the expression of PDLIM5 is associated with multiple mental disorders such as bipolar disorder, major depression, and susceptibility to schizophrenia (Liu et al, 2008;Zhao et al, 2009;Herrick et al, 2010;Wang et al, 2016). In the nervous system, PDLIM5 plays an important role in the formation of nerve growth cones and promotes the differentiation of nerve cells.…”
Section: The Expression Structure and Distribution Of Pdlim5mentioning
confidence: 99%
“…In addition, Edlund et al found that the increased expression of PDLIM5 is related to high tumor proliferation rates in non-small cell carcinoma ( Edlund et al, 2012 ). Steroids such as corticosteroid medications play an important role in the development of cancer; it has been reported that 25 single-nucleotide polymorphisms (SNPs) in PDLIM5 interact with steroids, thus affecting the occurrence and development of cancer ( Wang et al, 2016 ).…”
Section: The Differential Roles Of Pdlim5 In Various Organ Systemsmentioning
confidence: 99%